Monitoring the spread of swine enteric coronavirus diseases in the United States in the absence of a regulatory framework - Andres M Perez; Ana eAlba-Casals; Dane eGoede; Brian eMcCluskey; Robert eMorrison (Frontiers in Veterinary Science, 2016)
The reporting and monitoring of swine enteric coronavirus diseases (SECD), such as porcine epidemic diarrhea virus (PEDV) and porcine delta coronavirus (PDCoV), in the United States (US) has been challenging because of the absence of a regulatory framework and the emerging nature of these diseases. The National Animal Health Laboratory Network, the Emergency Management and the Response System and the Swine Health Monitoring Project were used to monitor the disease situation between May 2013 and March 2015. Important differences existed between and among them in terms of nature and extent of reporting. Here, we assessed the implementation of these systems from different perspectives, including a description and comparison of collected data, disease metrics, usefulness, simplicity, flexibility, acceptability, representativeness, timeliness and stability. This assessment demonstrates the limitations that the absence of premises identification imposes to certain databases, and the importance of federally-regulated frameworks in collecting accurate information on a timely-manner. This study also demonstrates the value that the voluntary and producer-organized systems may have in monitoring emerging diseases. The results from all three data sources help to establish the baseline information on SECD epidemiological dynamics after two years of disease spread in the country.